2020
DOI: 10.3961/jpmph.20.140
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Computed Tomography-based Abdominal Adiposity Indexes as Predictors of Non-alcoholic Fatty Liver Disease Among Middle-aged Korean Men and Women

Abstract: We compared the associations of 3 computed tomography (CT)-based abdominal adiposity indexes with non-alcoholic fatty liver disease (NAFLD) among middle-aged Korean men and women. Methods: The participants were 1366 men and 2480 women community-dwellers aged 30-64 years. Three abdominal adiposity indexes-visceral fat area (VFA), subcutaneous fat area (SFA), and visceral-to-subcutaneous fat ratio (VSR)-were calculated from abdominal CT scans. NAFLD was determined by calculating the Liver Fat Score from comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…We carried out this study to better understand the relationship between WC, subcutaneous fat depth, and the diagnosis of non-alcoholic liver disease. As expected, NAFLD was strongly correlated with WC and subcutaneous fat depth measurements, which is in line with previous research findings [ 26 , 27 , 28 , 29 , 30 ], suggesting that as liver attenuation values decrease, anthropometric values assessing obesity increase. In addition, we discovered a correlation between triglyceride and total cholesterol levels and liver attenuation values, indicating that the higher the lipid levels, the more intense the CT-determined steatosis.…”
Section: Discussionsupporting
confidence: 92%
“…We carried out this study to better understand the relationship between WC, subcutaneous fat depth, and the diagnosis of non-alcoholic liver disease. As expected, NAFLD was strongly correlated with WC and subcutaneous fat depth measurements, which is in line with previous research findings [ 26 , 27 , 28 , 29 , 30 ], suggesting that as liver attenuation values decrease, anthropometric values assessing obesity increase. In addition, we discovered a correlation between triglyceride and total cholesterol levels and liver attenuation values, indicating that the higher the lipid levels, the more intense the CT-determined steatosis.…”
Section: Discussionsupporting
confidence: 92%
“…The search from PubMed Central and ScienceDirect initially yielded 97,511 results altogether. After excluding duplicates and identifying records to be screened, 16,000 journals were screened by their title and abstracts for keywords before 50 full-text articles were assessed for 20 studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] eventually being accounted in this review.…”
Section: Search Resultsmentioning
confidence: 99%
“…6,[30][31][32] In this study, alcohol consumption showed an increased risk for developing overall EOC and MUC. Even though exercise might reduce adipose tissue, estrogen levels, and chronic inflammation 33,34 results of previous studies on physical activity and exercise have not been consistent. 6 According to a previous consortium study that included 8309 patients and 12,612 controls, physical inactivity was observed to have a significant risk for the overall incidence of EOC, along with the incidence of HGS, MUC, END, and CLC subtypes.…”
Section: Discussionmentioning
confidence: 94%